Penerapan Media Pembelajaran Berbasis Digital (Wordwall) untuk Meningkatkan Hasil Belajar Kognitif Peserta Didik Kelas IVA SDN 2 Setu Wetan - Zanzabila, Isqi; Wahyuningsih, Asih; Fauziyah, Nita (ARZUSIN, 2025)
Classroom learning should be conducted interactively, inspiratively, challengingly, enjoyably, and in a way that motivates students to learn. Digital-based learning media is necessary to create learning that not only adds knowledge but also increases students' interest in learning. Based on observations in Class IV A, it was found that the use of digital media is still minimal. Teachers often use conventional media, causing students to feel bored and unfocused while learning. This impacts students' learning outcomes, where during the pretest, there were seven students who did not achieve mastery. This study aims to improve students' learning outcomes on the topic of energy sources and their transformations using Wordwall learning media at SD Negeri 2 Setu Wetan in the 2024/2025 academic year. The benefit of this research is to assist students in enhancing their cognitive learning outcomes, which will impact their overall learning results. The classroom action research (CAR) design used is the Kemmis & McTaggart model, viewed as a cycle consisting of planning, action, observation, and reflection. The research cycle can be planned for two cycles or more, depending on the achievement of the planned success criteria. The cycles include pre-action, cycle I, cycle II, and subsequent cycles until the specified success is achieved. The data analysis technique used in this study is quantitative descriptive data analysis, which refers to the results of student evaluation tests. The results of the actions show a significant increase in students' learning outcomes from the pre-cycle, cycle I, to cycle II. The post-test results of cycle II show improvement, with 19 students (90%) achieving mastery, compared to 15 students (71%) in cycle I. The output of this research includes a draft article and the final report of the classroom action research that has been prepared. The next plan is to complete the process of publishing the scientific article. This classroom action research has yielded good results, indicating that the use of digital-based learning media makes it easier for students to understand the material and makes learning more engaging.